Book review: C. GASTGEBER - E. MITSIOU - J. PREISER-KAPELLER (ed.), The Register of the Patriarchate of Constantinople. An essential source for the history and Church of Late Byzantium. Wien 2013 - BLANCHET, Marie-Helene (Byzantina Symmeikta, 2015)
Book Review: C. GASTGEBER - E. MITSIOU- J. PREISER-KAPELLER (ed.), The Register of the Patriarchate of Constantinople. An essential source for the history and Church of Late Byzantium. Proceedings of the international Symposium, Vienna, 5th-9th May 2009 (Österreichische Akademie der Wissenschaften. Philosophisch-Historische Klasse. Denkschriften, 457. Band. Veröffentlichungen zur Byzanzforschung, 32. Band), Wien 2013, 308 p. ISBN 978-3-7001-7434-9.